Vascular Effects of Adrenomedullin and the Anti-Adrenomedullin Antibody Adrecizumab in Sepsis. Issue 2 (August 2018) - Geven, Christopher; Bergmann, Andreas; Kox, Matthijs; Pickkers, Peter
Abstract : ABSTRACT: Sepsis remains a major scientific and medical challenge, for which, apart from significant refinements in supportive therapy, treatment has barely changed over the last few decades. During sepsis, both vascular tone and vascular integrity are compromised, and contribute to the development of shock. The free circulating peptide adrenomedullin (ADM) is involved in the regulation of the endothelial barrier function and tone of blood vessels. Several animal studies have shown that ADM administration improves outcome of sepsis. However, in higher dosages, ADM administration may cause hypotension, limiting its clinical applicability. Moreover, ADM has a very short half-life and easily adheres to surfaces, further hampering its clinical use. The non-neutralizing anti-ADM antibody Adrecizumab (HAM8101) which causes a long-lasting increase of plasma ADM has shown promising results in animal models of systemic inflammation and sepsis; it reduced inflammation, attenuated vascular leakage, and improved hemodynamics, kidney function, and survival. Combined with an excellent safety profile derived from animal and phase I human studies, Adrecizumab represents a promising candidate drug for the adjunctive treatment of sepsis. In this review, we first provide a brief overview of the currently available data on the role of adrenomedullin in sepsis and describe its effects on endothelial barrier function and vasodilation. Furthermore, we provide a novel hypothesis concerning the mechanisms of action through which Adrecizumab may exert its beneficial effects in sepsis.